“SUKLIS” METODE INDIVIDU SEBAGAI UPAYA PENINGKATAN KINERJA GURU-GURU SD NEGERI 2 CAKRANEGARA - JOHANI JOHANI (GANEC SWARA, 2018)
This research is a School Action Research (PTS) with the aim to: improve the performance of teachers through activities "suklis" group method. Study time for 5 months in second semester of academic year 2017/2018 at SDN 2 Cakranegara. The subjects of the study were teachers at SDN 2 Cakranegara consisting of 4 teachers. The object of this research is "Suklis" (Clinical Supervision) with group method to improve teacher performance in learning process. The procedure in the study of this action essentially refers to the research design consisting of: 1) planning; 2) implementation; 3) observation; and 4) reflection on the result of action.Based on the result of the research, it can be concluded that; 1) Implementation measures "Suklis" to improve teacher performance in learning at SDN 2 Cakranegara are as follows: (a) Informing teachers about the implementation of "Suklis" activity on learning; (b) Preparing the guidance material in the form of implementation of learning accompanied by simulation; (c) Preparing the supervisory instruments; (d) Implement group supervision activities in the form of an office conference by not interrupting the learning activities; and e) Implement observation in the classroom when the teacher's learning activities are carried out; 2) Suklis "with the group method can improve teacher performance in teaching learning at SDN 2 Cakranegara. This is indicated by the increased performance of teachers both in the preparation stage and implementation of learning. This is demonstrated by the increase in performance attainment of 58% at baseline, to 76% at the end of Cycle I action, and increased to 90% in Cycle II action